2018
DOI: 10.3389/fvets.2018.00288
|View full text |Cite
|
Sign up to set email alerts
|

Galectins-1 and-3 Increase in Equine Post-traumatic Osteoarthritis

Abstract: Galectins are potent regulators of cell adhesion, growth and apoptosis in diverse cell types, including chondrocytes and synovial fibroblasts. Elevations in synovial fluid galectin-3 have been observed in rheumatoid arthritis, juvenile idiopathic arthritis and experimental inflammatory arthritis in animal models, whereas galectin-1 is thought to be protective. Less is known about galectins-1 and-3 in osteoarthritis (OA). Therefore, the purpose of this study was: (1) to determine whether galectin-1 and-3 synovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…21 It has been shown that galectin-1 levels markedly increased in serum of RA patients and positively correlated with disease activity score 28 (DAS-28) parameters. 48 Reesink et al 49 reported that galectin-1 levels increased with increasing osteoarthri- to compensate excessive inflammation. 50,51 No significant difference was found between study groups in terms of saliva concentration of galectin-1.…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been shown that galectin-1 levels markedly increased in serum of RA patients and positively correlated with disease activity score 28 (DAS-28) parameters. 48 Reesink et al 49 reported that galectin-1 levels increased with increasing osteoarthri- to compensate excessive inflammation. 50,51 No significant difference was found between study groups in terms of saliva concentration of galectin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial fluid samples were obtained from both limbs at the time of initial arthroscopy (day 0) and at days 5, 9, 12, 19, 26, 33, 61, and 75 post-operatively with aspiration volumes of approximately 2 ml per joint as described previously. 36 Synovial fluid samples were centrifuged at 3,000 g for 5 min immediately after collection, and synovial fluid supernatants were stored at −80°C until analysis. Prior to the surgery, each horse was acclimated to the treadmill for 1 to 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…Since horses are often kept in stables, physical inactivity may be a man-made reason for skeletal and joint diseases in horses. On other hand, the extensive training of a horse can lead to NCDs, e.g., post-traumatic osteoarthritis [104] and back problems [32]. Psychological disorders can evolve because of inappropriate housing management, weaning methods, and social or feeding restrictions [105][106][107].…”
Section: Non-communicable Diseasesmentioning
confidence: 99%